HYDROGEN’S POTENTIAL FOR SUSTAINABLE GLOBAL ENERGY DEVELOPMENT: INNOVATION AND TRADE DYNAMICS - YATSENKO, Olha; MORDAN, Vadym; IATSENKO, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The energy demands of modern society are growing alongside technological advancements, population increases, and economic progress. However, traditional energy sources such as oil, coal, and natural gas can no longer ensure sustainable development due to their finite nature and significant environmental impacts, including climate change, air, and water pollution. Renewable energy sources, particularly hydrogen energy, are becoming increasingly critical for securing a sustainable future. The article emphasizes that hydrogen is one of the key directions for developing renewable energy. Hydrogen is a versatile energy carrier with high energy density that can be produced from renewable sources and has minimal environmental impact. Its importance is rising due to the urgent need to decarbonize industries, transportation, and energy systems, in line with the requirements of international agreements and strategies to reduce carbon emissions. Demand for hydrogen is increasing as the hydrogen economy expands. In 2022, the global hydrogen market was valued at approximately 156 billion, and it is projected to grow to 385 billion by 2030, with a compound annual growth rate (CAGR) of 11.98% [1]. Leading players in the market include countries actively investing in hydrogen technologies, such as Japan, Germany, the United States, China, and South Korea. These nations focus on advancing electrolysis, developing hydrogen clusters, and integrating hydrogen into transportation systems. The article highlights that the development of modern hydrogen transportation and storage technologies is a critical factor. Hydrogen requires specific conditions for storage and transport, and innovative solutions—such as liquefied hydrogen, pipelines, and specialized containers-enhance transportation efficiency. This, in turn, reduces costs and increases the availability of hydrogen for use in energy systems. It is argued that the prospects for hydrogen energy include the potential to meet up to 18% of the world’s energy needs by 2050. Current investments, international initiatives, and advancements in hydrogen economy technologies open new opportunities for research and global collaboration, ensuring the continued development of hydrogen technologies and their increasing role in the global energy system.